2018
DOI: 10.1261/rna.067868.118
|View full text |Cite
|
Sign up to set email alerts
|

In vivo RNA structural probing of uracil and guanine base-pairing by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC)

Abstract: Many biological functions performed by RNAs arise from their in vivo structures. The structure of the same RNA can differ in vitro and in vivo owing in part to the influence of molecules ranging from protons to secondary metabolites to proteins. Chemical reagents that modify the Watson-Crick (WC) face of unprotected RNA bases report on the absence of base-pairing and so are of value to determining structures adopted by RNAs. Reagents have thus been sought that can report on the native RNA structures that preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…The passivation protocol was performed as in Methods section 'Passivation'. We validated the passivation with a range of EDC concentrations, 50-150mM, that are higher than the polyacrylic acid concentration of ~30mM (~0.2% polyacrylic acid); however, we didn't want the EDC concentration to be more than a few fold higher than the polyacrylic acid concentration as EDC can react with guanine in RNA (96), and therefore high concentrations of EDC may have undesired side effects. The reverse transcription reaction was performed with M-MuLV (enzymatics) according to the manufacturer's protocol, with 1.2kb Kanamycin Positive Control RNA (Promega) as a template, and random primers.…”
Section: Fig S1mentioning
confidence: 99%
“…The passivation protocol was performed as in Methods section 'Passivation'. We validated the passivation with a range of EDC concentrations, 50-150mM, that are higher than the polyacrylic acid concentration of ~30mM (~0.2% polyacrylic acid); however, we didn't want the EDC concentration to be more than a few fold higher than the polyacrylic acid concentration as EDC can react with guanine in RNA (96), and therefore high concentrations of EDC may have undesired side effects. The reverse transcription reaction was performed with M-MuLV (enzymatics) according to the manufacturer's protocol, with 1.2kb Kanamycin Positive Control RNA (Promega) as a template, and random primers.…”
Section: Fig S1mentioning
confidence: 99%
“…These results demonstrated the robustness of the method to perform structural analysis in a high-throughput pipeline and allowed determination of dissociation rate constants, K D s, for selected pools while eliminating single-clone biochemical assessment. This general workflow provides a unique framework which can be modified for all nucleic acids, including DNA and XNA aptamers, if base-specific modifications such as dimethyl sulfate (DMS), 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC), or nicotinoyl azide (NAz) probing are introduced (Feng et al, 2018;Kwok, Ding, Tang, Assmann, & Bevilacqua, 2013;Mitchell et al, 2018;Wang, Sexton, Culligan, & Simon, 2018;Zinshteyn et al, 2018).…”
Section: High-throughput Characterization Methodsmentioning
confidence: 99%
“…In summary, changes in transcript abundance, both within and between transcriptomes, appear intimately tied to changes in RNA structure. In the future, application of recent advances in our methodology, such as parallel probing with DMS and EDC, which is U-and G-specific (Wang et al 2018;Mitchell et al, 2019), to report on absence of base-pairing for all four nucleobases, will allow an improved description of the dynamic RNA structurome. Such experiments may elucidate specific structure-related motifs, facilitating delineation of more specific patterns and molecular mechanisms that underlie structurome and transcriptome (Walley and Dehesh, 2010) reshaping by abiotic stresses.…”
Section: Novel Concordancy Analysis Reveals Synergistic Roles Of Tranmentioning
confidence: 99%
“…Numerous chemicals have been identified that react with distinct regions of the RNA bases and sugarphosphate backbone (Mitchell et al, 2019;Leamy et al, 2016;Bevilacqua et al, 2016;Wilkinson et al, 2006;Ziehler and Engelke, 2000). These chemicals covalently modify RNA at the Watson-Crick (WC) face, the non-WC face or the ribose hydroxyl group.…”
Section: Introductionmentioning
confidence: 99%